ВПЛИВ BIFIDOBACTERIUM ANIMALIS SUBSP. LACTIS BB12 ТА LACTOBACILLUS RHAMNOSUS GG НА ПОЛЯРИЗАЦІЮ ПУХЛИНОАСОЦІЙОВАНИХ МАКРОФАГІВ - Fedosova, N.; Symchych, T.; Gogol, S.; Cheremshenko, N.; Virych, P.; Voyeykova, I.; Chekhun, V. (PH Akademperiodyka, 2026)
Background. The microbiota has a significant impact on the host’s immune system. However, the influence of the microbiome is heavily dependent on species, strain, and context. The aim of this study was to evaluate the influence of Bifidobacterium animalis subsp. lactis BB-12 (BB-12) and Lactobacillus rhamnosus GG (LGG) supplementation on the polarization of tumor-associated macrophages (TAMs) in mice with Ehrlich carcinoma. Materials and Methods. Female Balb/c mice bearing solid Ehrlich carcinoma were administered via gavage with BB-12, LGG, or 0.9% NaCl. On days 14, 21, and 28 of tumor growth, macrophages from tumor tissue were isolated and subjected to functional analysis. The nitric oxide (NO) production was measured using the standard Griess reaction. The arginase activity was determined based on the urea measurements. The reactive oxygen species (ROS) production was checked using flow cytometry. The cytotoxic activity was estimated by an MTT assay. Results. The application of different probiotic bacteria elicited different TAM polarization states. The TAMs in the group supplemented with LGG demonstrated M1 polarization with low arginase activity but high production of NO and ROS, as well as cytotoxic activity toward Ehrlich carcinoma cells. The TAMs of BB-12-treated mice exhibited M2 (supposedly M2b) polarization, characterized by high arginase activity alongside the preserved cytotoxic activity toward Ehrlich carcinoma cells in vitro. Conclusion. The results indicate that the consumption of two probiotics, BB-12 and LGG, affects the polarization of TAMs in distantly located experimental tumors.